Integrated Infection Control Practices Across Medical Departments: A Comprehensive Systematic Review - Alsallum, Khalid Sahal Salem; Lsloom, Mohammed Hussain Salam; Lasloom, Khaled Saleh Salem; ALSallum, Majed Sahal Salem; Alsallum, Salem Saleh Salem; Lasloom, Sahal Salem Abdullah; Lasloom, Jaber Asker M; Alyami, Awad Jaber Nasser (Journal of Posthumanism, 2024)
Healthcare-associated infections (HAIs) continue to pose a major threat to patient safety, requiring coordinated infection control strategies across all medical departments. This systematic review examines integrated infection control practices across emergency, outpatient, inpatient, surgical, and critical care settings. Studies published from 2016 to 2025 were analyzed to identify departmental variations, cross-cutting challenges, and evidence-based interventions that contribute to reducing HAIs. Findings highlight that although departments vary in workflow, patient acuity, and exposure risk, successful infection control programs share key features: strong leadership, standardized protocols, active surveillance, effective communication, and multidisciplinary collaboration. High-performing hospitals leverage technology—such as electronic monitoring systems, automated hand hygiene auditing, and AI-supported outbreak detection—to enhance compliance and response. The review concludes that infection prevention cannot be confined to isolated units; instead, integrated, organization-wide frameworks are critical to sustaining improved clinical outcomes. A unified infection control strategy improves patient safety, reduces antimicrobial resistance, and enhances overall healthcare quality. Recommendations emphasize governance structures, continuous staff training, monitoring systems, and harmonizing interdepartmental workflows to create resilient and high-reliability healthcare systems.